2021
DOI: 10.1182/blood.2020006287
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-intrinsic and -extrinsic determinants of response to blinatumomab in adults with B-ALL

Abstract: Blinatumomab, a bispecific antibody that directs CD3+ T cells to CD19+ tumor cells shows variable efficacy in B-progenitor acute lymphoblastic leukemia (B-ALL). To determine tumor-intrinsic and extrinsic determinants of response, we studied 44 adults with relapsed or refractory B-ALL (including two MRD positive) treated with blinatumomab using bulk tumor and single-cell sequencing. The overall response rate in patients with hematological disease was 55%, with a high response rate CRLF2-rearranged Ph-like ALL (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 32 publications
2
75
0
1
Order By: Relevance
“…For instance, in the phase 3 study, the remission rate including CR with full, partial, or incomplete hematologic recovery was 65.5% in R/R B-ALL patients with less than 50% of bone-marrow blasts, whereas it was only 34.4% for ≥50% [40]. A recent statistical study confirmed the negative correlation between disease burden and treatment response was statistically significant in R/R B-ALL patients treated with blinatumomab (P = 0.039) [94]. Moreover,…”
Section: Predictors Of Response To Bite Therapymentioning
confidence: 94%
See 1 more Smart Citation
“…For instance, in the phase 3 study, the remission rate including CR with full, partial, or incomplete hematologic recovery was 65.5% in R/R B-ALL patients with less than 50% of bone-marrow blasts, whereas it was only 34.4% for ≥50% [40]. A recent statistical study confirmed the negative correlation between disease burden and treatment response was statistically significant in R/R B-ALL patients treated with blinatumomab (P = 0.039) [94]. Moreover,…”
Section: Predictors Of Response To Bite Therapymentioning
confidence: 94%
“…The analysis of the relationship between tumor genetic features and treatment response is a useful way to select potential biomarkers for predicting outcomes of patients and guiding treatment decisions in the clinic. A recent study characterized the genetic profile in 44 adults with R/R B-ALL treated with blinatumomab to find out potential biomarkers to blinatumomab therapy [94]. Sixteen Ph-like patients with CRLF2 rearrangement had a higher response rate of 75%, whereas the response rate was 55% in the overall cohort.…”
Section: Gprc5d/ Cd3mentioning
confidence: 99%
“…Unfortunately, most patients still relapse eventually after primary response to blinatumomab therapy. These relapses are currently being extensively investigated and the data have thus far indicated that relapses are frequently found at immune-privileged extramedullary locations and some relapses have lost CD19 antigen expression, but more research is required to further elucidate these resistance mechanisms [ 18 , 19 ].…”
Section: Main Textmentioning
confidence: 99%
“…Interestingly, the expression levels of CD19 ex2part in malignant B cells resistant to blinatumomab were significantly higher than in those sensitive to blinatumomab, and the CD19 ex2part was higher in the recurrence sample after treatment than in the sample before treatment during blinatumomab therapy. The CD19 ex2part protein lacks residues Met1-Leu151, which is the domain recognized by blinatumomab [40] , suggesting that CD19 exon 2 encodes the epitope targeted by blinatumomab; therefore, CD19 ex2part and CD19 ∆ex2 may both be involved in resistance to blinatumomab. Then, exons 5 and 6 encode the transmembrane and cytosolic domains of the CD19 protein, promoting the secretion of CD19 ∆ex5–6 protein.…”
Section: Alternative Splicing Promotes Resistance To Targeted Drug Bymentioning
confidence: 99%